Alum catalyzed convenient synthesis of quino [2,3-b][1,5]benzoxazepine alpha-aminophosphonate derivatives - Sonar, Swapnil S.; Sadaphal, Sandip A.; Shitole, Nana N.; Jogdand, Nivrutti R.; Shingate, Bapurao B.; Shingare, Murlidhar S. (Bulletin of the Korean Chemical Society, 2009)
We have described an efficient synthesis of quino[2,3-b][1,5]benzoxazepine alpha-aminophosphonate derivatives by the nucleophilic addition of triethyl phosphite to substituted quino[2,3-b][1,5]benzoxazepines promoted by easily available, inexpensive and mild catalyst KAl(SO(4))(2)center dot 12H(2)O (alum). The reactions proceed smoothly at room temperature under solvent-free reaction conditions and providing high yield of product in very short reaction time.
Keywords: 5]benzoxazepine; alpha-Aminophosphonate; Alum; Quino[2.3-b][1; Solvent-free; Triethyl phosphite